ENVIRONMENTAL AND ECONOMIC STRATEGIES FOR SUSTAINABLE GROWTH IN UZBEKISTAN (Multidisciplinary Journal of Science and Technology, 2025)
This paper explores Uzbekistan’s recent environmental and economic strategies aimed at achieving sustainable growth. Through a qualitative analysis of government reports and recent journal articles, it highlights the country’s progress in renewable energy, sustainable agriculture, waste management, and legal reforms. Findings show measurable gains, including a rise in renewable energy capacity and improved waste recycling rates. However, challenges such as limited green financing and weak institutional coordination remain. The study concludes that with consistent policy support and investment, Uzbekistan can successfully transition toward a green economy that balances development with environmental preservation.